Upaya Mitigasi Bagi Small Island Developing States (SIDS) Berbasis Renewable Energy Melalui Kerangka Unfccc Untuk Menekan Dampak Perubahan Iklim - Dodi Roikardi; Siti Muslimah; Diah Apriani Atika Sari (Faculty of Law Universitas Sebelas Maret, 2018)
The main issue in this research is about climate change phenomenon that causes several bad impacts to small island countries which also be known as Small Island Developing States (SIDS). According to those characteristics, SIDS countries is the most vulnerable parties of the climate change impacts. Therefore, several mitigation acts needed for reducing climate change impacts. International Climate Change Law has ruled mitigation acts in several law instruments, such as United Nations Framework Convention on Climate Change (UNFCCC) 1992, Kyoto Protocol 1997, and Paris Agreement 2015. Pacific and Caribbean SIDS has choosen renewable energy deployment as a part of its national mitigation, because they highly depended on the use of fossil fuels which is considered as climate change contributor for power generation. Pacific and Caribbean SIDS have taken mitigation measures based on renewable energy and already achieved its output, but there are still barriers such as low funding, lack of national law instruments that support its mitigation measures, and technical problems including the lack of technologies and human resources. So, SIDS should take several measures to eliminate these barriers for achieving the main purposes of climate change mitigation optimally.